2013
DOI: 10.1371/journal.pone.0065599
|View full text |Cite
|
Sign up to set email alerts
|

Role of NK Cell Subsets in Organ-Specific Murine Melanoma Metastasis

Abstract: Tumor metastasis plays a major role in the morbidity and mortality of cancer patients. Among solid tumors that undergo metastasis, there is often a predilection to metastasize to a particular organ with, for example, prostate cancer preferentially metastasizing to bones and colon cancer preferentially metastasizing to the liver. Although many factors are thought to be important in establishing permissiveness for metastasis, the reasons for organ-specific predilection of each tumor are not understood. Using a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…6 Our data have shown for the first time that a significantly high number of CD27 NK cells are preferentially recruited into the B16F10-induced melanoma tumor microenvironment at an early stage. Our data are in contrast with previous report by Lakshmikanth et al which observed very few NK cells among leukocytes in mouse primary melanomas.…”
Section: Cd11bmentioning
confidence: 55%
See 1 more Smart Citation
“…6 Our data have shown for the first time that a significantly high number of CD27 NK cells are preferentially recruited into the B16F10-induced melanoma tumor microenvironment at an early stage. Our data are in contrast with previous report by Lakshmikanth et al which observed very few NK cells among leukocytes in mouse primary melanomas.…”
Section: Cd11bmentioning
confidence: 55%
“…4 Infiltration of NK cells has been observed in several types of tumors such as fibrosarcoma, renal cell carcinoma, gastrointestinal sarcoma, and breast tumors. 5,6 The CD27…”
Section: Cd11bmentioning
confidence: 99%
“…In addition, NK cells at distinct anatomic locations inhibit B16 using different mechanisms. For example, liver NK cells, but not lung NK cells, rely on perforin-dependent pathways for destruction of B16 (46).…”
Section: Discussionmentioning
confidence: 99%
“…These features may protect B16 from direct NK cell cytolysis. It is also noteworthy that NK cells isolated directly ex vivo are only poorly cytotoxic against B16, unless isolated from hosts systemically activated with polyinosinic-polycytidylic acid or CpG (46,49).…”
Section: Discussionmentioning
confidence: 99%
“…2 NK cells also have immunoregulatory features, including the secretion of cytokines and chemokines and cell-to-cell cross-talk, 3,4 and are important in defending against viral infections and controlling tumor growth. 5,6 The activities of NK cells are regulated through activating and inhibiting receptors, which determine the course of action of these cells. 7 NK cells are activated through distress via the detection of stress-induced ligands on target cells by NK cytotoxicity receptors, which include NKp30, NKp44, NKp46 and C-type lectin receptors, such as NKG2D.…”
Section: Introductionmentioning
confidence: 99%